PENGGUNAAN GAYA KOMUNIKASI INSANI MENURUT AL-QUR’AN (DITINJAU DARI ILMU BALAGHAH) - Muhamad Faizin (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2022)
In the Al-Qur'an there are many verses that command to speak with words that are in accordance with the ethics of communication in Islam. Such as: Qaulan Ma'ruufa, Qaulan Kariima, Qaulan Baligha, Qaulan Maisuuro, Qaulan Sadiida, Qaulan Layyina and other similar sentences.The purpose of this study is to find out in more detail about the branch of balaghah science, namely in the Qur'an which is related to the style of language for communication and strengthened by the views of commentators in his work in the field of interpretation. And in the Science of Balaghah, we study the use of communication language styles that are adapted to situations and conditions. The results of the research that has been carried out are about the comparison between the use of the word good communication and the use of the word communication that is not good, then contributions from all sides, that in any activity, the Qur'an has taught good communication, so this can be applied in the world of education or family education and study of the style of language used by the Qur'an in conveying its aims and objectives in communicating contains an element of its own beauty, because its use is adapted to situations and conditions. This research is included in qualitative research. The conclusion of this study is that the characteristics of polite language according to the six principles of Islamic communication in the Qur'an are utterances that have values: 1) truth, 2) honesty, 3) justice, 4) kindness, 5) straight, 6) smooth, 7 ) polite, 8) appropriate, 9) respectful, 10) solemn, 11) optimistic, 12) beautiful, 13) pleasant, 14) logical, 15) eloquent, 16) bright, 17) precise, 18) heartfelt, 19) in tune, 20) imposing, 21) calm, 22) effective, 23) mild, 24) generous, 25) gentle, 26) humble. When viewed in terms of degree, we will rank them as karima or noble, ma'rufa or good, layyina or gentle, baligha or precise, maysura or easy, and sadida or righteous. In the six principles of communication styles in the Qur'an that have been described above, when viewed from the science of balaghah, all words like anything must use a good communication style.